Society needs experts with climate change competencies – what is the role of higher education in atmospheric and Earth system sciences? - Laura Riuttanen; Taina Ruuskanen; Mikko Äijälä; Anniina Lauri (Tellus: Series B, Chemical and Physical Meteorology, 2021)
The urgent societal need for climate action requires climate change expertise. But who is a climate change expert? What is the role of atmospheric and Earth system science education? In this study, we examine what competencies do atmospheric and Earth system scientists teach in selected programmes in seven European countries, and how they view the importance of various competencies for the students to learn. We also asked about teacher experiences and wishes related to teaching collaboration. We found that the atmospheric and Earth system scientists taught and valued the highest the traditional academic competencies related e.g. to critical thinking and applying knowledge. The normative, strategic and interpersonal competencies of sustainability were generally less valued and taught. The largest teaching gaps were found in competencies such as developing new ideas, interpersonal competency, making arguments and looking for solutions, critical thinking, collaboration and communication skills. Preferred collaborators for atmospheric and Earth system scientists were scientists from their own field or from other natural sciences, while collaborators from other sciences and wider society were less popular choices. The atmospheric and Earth systems scientists in our study did not see themselves as climate change experts. We foresee here a need to define climate change competencies.